BNF 73 : march - september 2017 - British National Formulary; Joint Formulary Committee (London : Pharmaceutical Press, 2017)
BNF 73 (March 2017) is the authoritative guide to prescribing, dispensing and administering medicines for all healthcare professionals.
Includes index.
Keywords: Drugs and sport; Pharmacology; Medical Reference Books